A bird-type protective net and a production process thereof
Patent Information
- Application Number
- CN202611177487.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]解决的技术问题:针对现有技术存在的聚乳酸纤维防护网强度不足、耐老化性能差、与天然纤维界面结合弱以及功能单一的问题,本发明通过一种亲鸟型防护网的生产工艺及亲鸟型防护网,实现多组分化学协同增强、界面强结合及多功能集成
1、本发明通过对麻纤维进行碱处理与硅烷偶联剂接枝改性,显著提高了麻纤维与聚乳酸基体之间的界面相容性,改性麻纤维表面的硅羟基能够与聚乳酸分子链末端的羧基形成化学键合,同时与巯基化氧化石墨烯上的极性官能团产生分子间作用力,三者共同形成“聚乳酸-改性麻纤维-巯基化氧化石墨烯”三维交织增强网络。
Abstract
Description
Technical Field
[0001] This invention relates to the field of polylactic acid (PLA) protective netting technology, specifically to a bird-friendly protective netting and its manufacturing process. Background Technology
[0002] Protective netting is widely used in forestry seedling cultivation, ecological restoration, and agricultural planting. Its main functions are to prevent birds from pecking at seedlings and to prevent wild animals from trampling on them, while also meeting the basic requirements of ventilation and light transmission. Traditional protective netting is mostly woven from petroleum-based synthetic fibers such as polyethylene and polypropylene. Although these materials have good mechanical properties and weather resistance, their non-degradable nature causes discarded netting to remain in the natural environment for a long time, causing white pollution and ecological hazards. In recent years, biodegradable polymer materials, represented by polylactic acid (PLA), have been gradually introduced into the field of protective netting. However, pure PLA fibers have inherent defects such as insufficient strength, poor aging resistance, and weak interfacial bonding with natural fibers, which limit their application in long-term outdoor service scenarios.
[0003] In existing technologies, researchers have attempted to improve the mechanical properties of polylactic acid (PLA) matrices by adding nanofillers or natural fiber reinforcement. However, most solutions focus only on the modification of a single component, failing to fully consider the chemical compatibility and synergistic mechanisms between the reinforcing phases. Furthermore, existing functional coating designs for protective netting often remain at a single-function level, either focusing solely on bird deterrence or attraction, or solely pursuing self-cleaning properties. They lack systematic solutions that integrate multiple functions such as bird attraction, self-cleaning, and antibacterial properties. Moreover, the coating and substrate are mostly physically adhered, making it difficult to meet the requirements for long-term outdoor use in terms of water resistance and weather resistance.
[0004] Therefore, there is an urgent need to develop a production process for bird-friendly protective nets that can achieve multi-component chemical synergy, strong interfacial bonding, and functional integration, in order to overcome the comprehensive bottlenecks of existing technologies in terms of mechanical properties, interfacial compatibility, functional diversity, and controllable degradation. Summary of the Invention
[0005] Technical problems to be solved: In view of the problems of insufficient strength, poor aging resistance, weak interfacial bonding with natural fibers, and single function of existing polylactic acid fiber protective nets, this invention achieves multi-component chemical synergistic enhancement, strong interfacial bonding and multi-functional integration through a bird-friendly protective net production process and bird-friendly protective net.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A manufacturing process for a bird-friendly protective net, the manufacturing process comprising the following steps: S1. Prepare modified hemp fiber, modified nano-titanium dioxide, mercapto-modified graphene oxide and stearic acid-modified nano-calcium carbonate for later use. S2. Weigh 40-45 parts by weight of polylactic acid, 35-45 parts by weight of modified hemp fiber, 2-3 parts by weight of modified nano-titanium dioxide, 1-2 parts by weight of thiolized graphene oxide, 2-3 parts by weight of stearic acid modified nano-calcium carbonate, 8-12 parts by weight of heavy calcium carbonate, 0.2-0.7 parts by weight of light stabilizer, 1-5 parts by weight of antioxidant component, 5-7 parts by weight of flame retardant and 5-8 parts by weight of degradation regulator and mix them. Then, melt-blend and granulate the mixture using a twin-screw extruder at 150-220℃ to obtain blended chips. The screw speed of the twin-screw extruder is 100-350 r / min, the length-to-diameter ratio is 28:1, and the compression ratio is 7:2. S3. The blended chips are first pre-crystallized at 60-65℃ for 3-4 hours, and then dried at 100℃ for 15 hours to make the moisture content less than 0.005wt%. After drying, the chips are melt-spun at 195℃ and the initial web is obtained by drawing. The spinning speed is 1000m / min and the drawing ratio is 3. S4. Apply the functional coating liquid to the surface of the nascent net wire at an impregnation coating amount of 8-15%. After drying, weave the net and tension it to set the shape. The result is a bird-friendly protective net. The drying method is to first dry it at 80℃ for 5 minutes, and then bake it at 140-150℃ for 3 minutes. During the weaving process, the coated net wire should be wound with low tension to avoid coating wear.
[0007] Furthermore, the preparation method of the modified hemp fiber in S1 is as follows: The hemp fiber was immersed in a sodium hydroxide solution with a concentration of 5 g / L at a bath ratio of 1:20 (g / mL) and boiled for 1-3 hours. After draining, it was immersed in an ethanol hydrolysate of silane coupling agent KH-560 at a bath ratio of 1:20 (g / mL) for 4 hours. After draining, it was placed in a vacuum drying oven at 50℃ and dried for 8 hours. The result is the modified hemp fiber.
[0008] The preparation method of ethanol hydrolysate of silane coupling agent KH-560 is as follows: 1 part by weight of silane coupling agent KH-560 is dispersed in 100 parts by weight of 80% ethanol aqueous solution. After stirring at a stirring speed of 400-500 r / min for 30 min, 1 part by weight of 0.1 mol / L hydrochloric acid solution is added, and stirring is continued for 10 min. The resulting product is ethanol hydrolysate of silane coupling agent KH-560.
[0009] Furthermore, the preparation method of modified nano-titanium dioxide in S1 is as follows: Ten parts by weight of nano-titanium dioxide were poured into 100 parts by weight of anhydrous ethanol and ultrasonically dispersed at 300W for 15 minutes. The pH value was then adjusted to 4.0-5.0. Next, 0.15-0.2 parts by weight of silane coupling agent KH-550 were added. The mixture was stirred at 200-300 r / min at 65℃ for 1-2 hours. After the reaction was completed, the filtrate was removed by centrifugation and washed three times with anhydrous ethanol. The filtrate was then dried in a vacuum drying oven at 80℃ for 12 hours. The resulting product was modified nano-titanium dioxide.
[0010] Furthermore, the preparation method of thiolized graphene oxide in S1 is as follows: Under nitrogen protection, 1-2 parts by weight of graphene oxide and 10-20 parts by weight of thiourea are dissolved in 150-300 parts by weight of 40% hydrobromic acid solution. After stirring at room temperature for 20-30 minutes, the mixture is refluxed at 50-60℃ for 12-15 hours. After cooling to room temperature, the mixture is reacted at 0-5℃ for 20-30 minutes. 400 parts by weight of 20% sodium hydroxide solution are added, and the mixture is reacted at room temperature for 8 hours. The pH is adjusted to 2-3 with 10% hydrochloric acid solution, and the mixture is recrystallized with deionized water. After vacuum drying in a vacuum drying oven at 45-50℃ for 12 hours, the resulting product is thiolized graphene oxide.
[0011] Furthermore, the preparation method of stearic acid modified nano-calcium carbonate in S1 is as follows: Weigh 80-100 parts by weight of nano-calcium carbonate with a particle size of 20-200 nm and disperse it in deionized water. After the dispersion is uniform, add 2.1-2.5 parts by weight of stearic acid. Heat to 90℃ and stir at 2500 r / min for 40 min. After filtering to remove the filtrate, wash with deionized water 3-5 times. Place in a drying oven at 100℃ and dry for 2-3 h. Then pulverize and pass through a 325 mesh sieve. The result is stearic acid modified nano-calcium carbonate.
[0012] Furthermore, in S2, the light stabilizer is a hindered amine light stabilizer, the antioxidant component is a compound of antioxidant 1010 and antioxidant 168 mixed in equal weight ratio, the flame retardant is a compound of aluminum hydroxide and magnesium hydroxide mixed in a weight ratio of 3:2, and the degradation regulator is potato starch.
[0013] Furthermore, the preparation method of the functional coating liquid in S4 is as follows: Weigh 10-20 parts by weight of plant essential oil microcapsule emulsion and 85-100 parts by weight of inorganic hydrophilic coating dispersion and mix them. Add 2-8 parts by weight of nano zinc oxide and stir at a stirring speed of 600-800 r / min for 10 min to mix and disperse. The result is the functional coating liquid.
[0014] Furthermore, the preparation method of the plant essential oil microcapsule emulsion is as follows: Rosemary essential oil, peppermint essential oil, and lemongrass essential oil are mixed in equal volume ratios and recorded as a plant essential oil mixture. Then, 60-90 parts by weight of deionized water, 5-20 parts by weight of the plant essential oil mixture, and 1-4 parts by weight of sodium dodecylbenzenesulfonate are weighed and mixed. After high-speed shearing at a stirring speed of 4000-8000 r / min for 10-20 min, the resulting product is a plant essential oil microcapsule emulsion.
[0015] Furthermore, the preparation method of the inorganic hydrophilic coating dispersion is as follows: Under stirring conditions of 100-200 r / min, add 5-10 parts by weight of silica sol with a SiO2 content of 25-30% to 80-90 parts by weight of deionized water, then add 0.1-0.3 parts by weight of sodium hexametaphosphate and 0.1-0.3 parts by weight of sodium benzenesulfonate, adjust the pH value to 8.5-10.0 and continue stirring for 30 min. The result is a silica hydrosol solution. Add 5-15 parts by weight of attapulgite to 70-95 parts by weight of silica hydrosol solution, stir to dissolve, then add 3-10 parts by weight of potassium dihydrogen phosphate and 1-2 parts by weight of sodium alginate. Stir and disperse at a stirring speed of 800-1000 r / min to obtain the inorganic hydrophilic coating dispersion.
[0016] This invention provides a bird-friendly protective net and its manufacturing process. Compared with existing technologies, this invention has the following advantages: 1. This invention significantly improves the interfacial compatibility between hemp fibers and polylactic acid (PLA) matrix by alkali treatment and silane coupling agent grafting modification of hemp fibers. The silanol groups on the surface of the modified hemp fibers can form chemical bonds with the carboxyl groups at the ends of the PLA molecular chains, and at the same time generate intermolecular forces with the polar functional groups on the mercapto-modified graphene oxide. The three together form a three-dimensional interwoven reinforcement network of "PLA-modified hemp fibers-mercapto-modified graphene oxide".
[0017] The thiol groups introduced onto the thiolized graphene oxide can not only undergo ring-opening grafting reactions with the ester groups on the polylactic acid molecular chain, but also form Ti-S coordination chelate bonds with the titanium hydroxyl groups on the surface of the modified nano-titanium dioxide. This bidentate chelate structure greatly enhances the bonding strength of the inorganic-organic interface, allowing the inorganic nanoparticles to form "anchoring points" in the matrix, effectively hindering the relative slippage of polymer chains and crack propagation. Meanwhile, after the stearic acid-modified nano-calcium carbonate is uniformly dispersed in the matrix, its long-chain alkyl groups become physically entangled with the polylactic acid molecular chain. The nano-calcium carbonate particles themselves act as rigid fillers, forming a "nano-micro" multi-scale rigid framework with the heavy calcium carbonate, which not only enhances the impact toughness of the matrix but also improves processing fluidity through the lubricating effect of the stearic acid layer.
[0018] The above four modified components are indispensable: without thiolized graphene oxide, Ti-S chelate anchoring cannot be formed, and the reinforcing effect of modified nano-titanium dioxide will be greatly weakened; without modified hemp fiber, a three-dimensional interwoven network cannot be constructed, and the matrix strength and modulus will decrease significantly; without stearic acid modified nano-calcium carbonate, the rigid skeleton is incomplete and the impact toughness is insufficient; the reinforcing effect produced by the synergy of the four far exceeds the simple sum of the effects of each component acting alone, and achieves a simultaneous leap in matrix strength, toughness and aging resistance.
[0019] 2. In the functional coating liquid coated on the surface of the network cable in this invention, the plant essential oil microcapsule emulsion, the inorganic hydrophilic coating dispersion, and the nano zinc oxide constitute a ternary synergistic system of "continuous bird attraction - hydrophilic self-cleaning - photocatalytic antibacterial". After the coating is cured, the plant essential oil microcapsule emulsion forms a core-shell structure microcapsule. The shell layer acts as a physical barrier and slow-release regulation for the essential oil molecules, so that the volatile bird-attracting components of rosemary essential oil, peppermint essential oil, and lemongrass essential oil can achieve long-term and stable release in the natural environment, avoiding the problem of rapid volatilization and failure caused by directly adding essential oils. Meanwhile, the silica hydrosol in the inorganic hydrophilic coating dispersion cross-links with attapulgite to form a hydrophilic network structure with micro-nano pores. This structure, on the one hand, adsorbs moisture from the air onto the coating surface through capillary effect to form a continuous water film, giving the mesh excellent hydrophilic self-cleaning function, allowing bird droppings, dust and other pollutants attached to the mesh to automatically slide off under the action of the water film; on the other hand, the porous structure of attapulgite can adsorb essential oil molecules released from plant essential oil microcapsules, playing a "reservoir-slow release" buffering role, making the release curve of the bird repellent component smoother and longer-lasting.
[0020] The introduction of nano-zinc oxide achieves a triple synergistic effect: First, the zinc ions on the surface of nano-zinc oxide can form zinc phosphate coordination chelates with the phosphate ions dissociated from potassium dihydrogen phosphate in the inorganic hydrophilic coating, firmly anchoring the nano-zinc oxide in the coating network framework and enhancing the structural stability of the coating; Second, nano-zinc oxide generates photogenerated electron-hole pairs under sunlight irradiation, possessing broad-spectrum antibacterial and photocatalytic degradation capabilities for organic pollutants, forming a dual purification mechanism of "photocatalytic degradation + water film rinsing" with the hydrophilic self-cleaning function; Third, the oxygen vacancies on the surface of nano-zinc oxide can form weak coordination adsorption with polar groups such as hydroxyl and carbonyl groups in plant essential oil molecules, further regulating the release rate of essential oils, changing their release behavior from "rapid burst release" to "slow constant release," and significantly extending the effective period.
[0021] The functional coating system is not isolated from the substrate material. The unreacted thiol groups on the thiolized graphene oxide in the substrate can form Zn-S coordination bonds with zinc ions on the surface of nano-zinc oxide in the coating. At the same time, during the coating and baking process, the silica sol particles in the coating can penetrate into the micropores on the surface of the mesh and form a Si-O-Ca bridging structure with calcium ions on the surface of modified nano-calcium carbonate in the substrate. This results in a chemical bonding interface between the coating and the substrate, rather than simple physical adhesion, which significantly improves the adhesion strength and water resistance of the coating.
[0022] 3. This invention constructs a multi-layered chelate cross-linking network within the matrix and at the coating-matrix interface. This is the core technology for achieving a unified high strength, long lifespan, and controllable degradation of the protective mesh. Within the matrix, thiolized graphene oxide plays a triple bridging role: the carboxyl groups on its backbone form carboxylate-titanium chelate bonds with the titanium hydroxyl groups on the surface of modified nano-titanium dioxide; the thiol groups form Ti-S coordination bonds with the titanium hydroxyl groups; and the graphene backbone itself forms π-π stacking and hydrophobic interactions with the polylactic acid molecular chains, making graphene oxide a "multifunctional cross-linking node" connecting inorganic nanoparticles and organic polymer matrices.
[0023] Modified nano-titanium dioxide serves as another key crosslinking center. Its surface titanium atoms simultaneously form multiple coordination chelates with the thiol and carboxyl groups on the thiolized graphene oxide and the hydroxyl groups at the ends of the polylactic acid molecular chains. A single titanium center can bind to multiple ligands simultaneously, constructing a three-dimensional coordination crosslinking network with titanium as its core. The introduction of modified nano-calcium carbonate further enriches the chelate network hierarchy. Its surface calcium ions form carboxylic acid calcium coordination bonds with the carboxyl groups on the thiolized graphene oxide and calcium-oxygen weak coordination interactions with the ester carbonyl groups on the polylactic acid molecular chains. Acting as "flexible crosslinking points" in the system, it enhances the connection density between molecular chains without causing material embrittlement due to excessive crosslinking.
[0024] Meanwhile, potato starch, a degradation regulator in the system, is preferentially degraded by microorganisms in the soil microbial environment, creating a localized acidic microenvironment and enzymatic effects that trigger a chain reaction of polylactic acid bond hydrolysis. Meanwhile, heavy calcium carbonate and nano-calcium carbonate gradually dissolve under acidic conditions, releasing calcium and carbonate ions that neutralize the local acidity, maintaining the pH value within the matrix within a suitable range for moderate polylactic acid hydrolysis and preventing uncontrolled degradation due to autocatalytic acidification. More importantly, the thiolized graphene oxide is gradually oxidized and stripped during degradation, causing the Ti-S chelate bonds between it and nano-titanium dioxide to break. The cross-linked network gradually transforms from "strong cross-linking" to "weak cross-linking." This gradual network disintegration process occurs simultaneously with the decrease in the molecular weight of the polylactic acid matrix, achieving a "gradual decline" rather than a "precipitous drop" in the mechanical properties of the protective network. This ensures sufficient strength during its intended service life and allows for rapid entry into a controlled degradation phase after the service life expires. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0026] The present invention will be further described below with reference to embodiments.
[0027] Example 1: A manufacturing process for a bird-friendly protective net in this example includes the following steps: S1. Prepare modified hemp fiber, modified nano-titanium dioxide, mercapto-modified graphene oxide, and stearic acid-modified nano-calcium carbonate for later use.
[0028] The preparation method of modified hemp fiber in S1 is as follows: The hemp fiber was immersed in a sodium hydroxide solution with a concentration of 5 g / L and boiled for 1 hour at a bath ratio of 1:20 (g / mL). After draining, it was immersed in an ethanol hydrolysate of silane coupling agent KH-560 at a bath ratio of 1:20 (g / mL) for 4 hours. After draining, it was placed in a vacuum drying oven at 50°C and dried for 8 hours. The result is the modified hemp fiber.
[0029] The preparation method of the ethanol hydrolysate of silane coupling agent KH-560 is as follows: 1 part by weight of silane coupling agent KH-560 is dispersed in 100 parts by weight of 80% ethanol aqueous solution, stirred at 400 r / min for 30 min, then 1 part by weight of 0.1 mol / L hydrochloric acid solution is added, and stirring is continued for 10 min to obtain the ethanol hydrolysate of silane coupling agent KH-560.
[0030] By removing impurities such as pectin and lignin from the surface of hemp fibers through alkali treatment, abundant cellulose hydroxyl groups are exposed. Then, epoxy groups are introduced by grafting with KH-560, which enables them to chemically bond with polylactic acid matrix in subsequent processing, thereby solving the problem of poor compatibility between natural fibers and hydrophobic polyesters.
[0031] The preparation method of modified nano-titanium dioxide in S1 is as follows: Ten parts by weight of nano-titanium dioxide were poured into 100 parts by weight of anhydrous ethanol and ultrasonically dispersed at 300W for 15 minutes. The pH was then adjusted to 4.0. Next, 0.15 parts by weight of silane coupling agent KH-550 were added, and the mixture was stirred at 200 r / min for 1 hour at 65°C. After the reaction was completed, the filtrate was removed by centrifugation and washed three times with anhydrous ethanol. The filtrate was then dried in a vacuum drying oven at 80°C for 12 hours to obtain modified nano-titanium dioxide. This step utilizes the condensation of amino groups on the surface of KH-550 with hydroxyl groups on the surface of nano-titanium dioxide to impart organic reactivity to the inorganic particles and prevent their aggregation in the polymer matrix.
[0032] The preparation method of thiolized graphene oxide in S1 is as follows: Under nitrogen protection, 1 part by weight of graphene oxide and 10 parts by weight of thiourea were dissolved in 150 parts by weight of a 40% hydrobromic acid solution. The mixture was stirred at room temperature for 20 min, then refluxed at 50°C for 12 h. After cooling to room temperature, the mixture was reacted at 0°C for 20 min. 400 parts by weight of a 20% sodium hydroxide solution were added, and the reaction was carried out at room temperature for 8 h. The pH was adjusted to 2 with a 10% hydrochloric acid solution, and the mixture was recrystallized with deionized water. The resulting product was vacuum dried in a 45°C vacuum drying oven for 12 h to obtain thiolized graphene oxide. This reaction successfully grafted thiol groups onto the edges and defect sites of graphene oxide sheets, providing active sites for subsequent coordination bonding with titanium species.
[0033] The preparation method of stearic acid modified nano-calcium carbonate in S1 is as follows: 80 parts by weight of 20 nm nano-calcium carbonate were dispersed in deionized water. After uniform dispersion, 2.1 parts by weight of stearic acid were added. The mixture was heated to 90°C and stirred at 2500 rpm for 40 min. After filtering to remove the filtrate, the mixture was washed three times with deionized water and dried in a 100°C drying oven for 2 h. Finally, it was pulverized and passed through a 325-mesh sieve. The resulting product is stearic acid-modified nano-calcium carbonate. The stearic acid coating not only improves the oleophilicity of the nano-calcium carbonate but also acts as an internal lubricant, helping to reduce the melt viscosity.
[0034] S2. Weigh 40 parts by weight of polylactic acid, 35 parts by weight of prepared modified hemp fiber, 2 parts by weight of modified nano titanium dioxide, 1 part by weight of mercapto-modified graphene oxide, 2 parts by weight of stearic acid modified nano calcium carbonate, 8 parts by weight of heavy calcium carbonate, 0.2 parts by weight of light stabilizer, 1 part by weight of antioxidant component, 5 parts by weight of flame retardant and 5 parts by weight of degradation regulator and mix them. Then, melt-blend and granulate the mixture at 150°C using a twin-screw extruder to obtain blended chips. The screw speed of the twin-screw extruder is 100 r / min, the length-to-diameter ratio is 28:1 and the compression ratio is 7:2.
[0035] In S2, the light stabilizer is a hindered amine light stabilizer, the antioxidant component is a compound of antioxidant 1010 and antioxidant 168 mixed in equal weight ratio, the flame retardant is a compound of aluminum hydroxide and magnesium hydroxide mixed in a weight ratio of 3:2, and the degradation regulator is potato starch.
[0036] S3. The blended chips are first pre-crystallized at 60℃ for 3 hours, and then dried at 100℃ for 15 hours to make the moisture content less than 0.005wt%. After drying, the chips are melt-spun at 195℃ and the initial web is obtained by drawing. The spinning speed is 1000m / min and the drawing ratio is 3. S4. Apply the functional coating liquid to the surface of the nascent net wire at an 8% impregnation coating amount. After drying, weave it into a net and tension it to set the shape. The result is a bird-friendly protective net. The drying method is to first dry it at 80°C for 5 minutes, and then bake it at 140°C for 3 minutes. During the weaving process, the coated net wire adopts a low-tension winding method to avoid coating wear.
[0037] The preparation method of the functional coating liquid in S4 is as follows: Weigh 10 parts by weight of plant essential oil microcapsule emulsion and 85 parts by weight of inorganic hydrophilic coating dispersion and mix them. Add 2 parts by weight of nano zinc oxide and stir at 600 r / min for 10 min to mix and disperse. The result is the functional coating liquid.
[0038] The preparation method of the plant essential oil microcapsule emulsion is as follows: Rosemary essential oil, peppermint essential oil, and lemongrass essential oil were mixed in equal volume ratio and recorded as a plant essential oil mixture. Then, 60 parts by weight of deionized water, 5 parts by weight of the plant essential oil mixture, and 1 part by weight of sodium dodecylbenzenesulfonate were weighed and mixed. After high-speed shearing at a stirring speed of 4000 r / min for 10 min, the resulting product was the plant essential oil microcapsule emulsion.
[0039] The preparation method of inorganic hydrophilic coating dispersion is as follows: Under stirring conditions of 100 r / min, 5 parts by weight of silica sol with a SiO2 content of 25% were added to 80 parts by weight of deionized water, followed by 0.1 parts by weight of sodium hexametaphosphate and 0.1 parts by weight of sodium benzenesulfonate. After adjusting the pH value to 8.5, stirring was continued for 30 min. The resulting silica hydrosol solution was obtained. Add 5 parts by weight of attapulgite to 70 parts by weight of silica hydrosol solution, stir to dissolve, then add 3 parts by weight of potassium dihydrogen phosphate and 1 part by weight of sodium alginate. Stir and disperse at a stirring speed of 800 r / min to obtain the inorganic hydrophilic coating dispersion.
[0040] Under the parameters of this embodiment, a stable three-dimensional interwoven reinforcement network of "polylactic acid-modified hemp fiber-thiolized graphene oxide" is formed among the components. Specifically, although this embodiment uses the lower limit ratio of each component, the thiol groups on the thiolized graphene oxide can still effectively form Ti-S coordination chelate bonds with the titanium hydroxyl groups on the surface of the modified nano-titanium dioxide. This bidentate chelate structure, as a key "anchor point," firmly locks the inorganic nanoparticles between the polylactic acid molecular chains, hindering the relative slippage of the polymer chains.
[0041] Simultaneously, the silanol groups on the surface of the modified hemp fiber undergo esterification with the carboxyl groups at the ends of polylactic acid, and form hydrogen bonds with the polar functional groups on the mercapto-modified graphene oxide, constructing a rigid framework that runs through the matrix. Stearic acid-modified nano-calcium carbonate plays a dual role in the system: its long stearic acid chains physically entangle with the polylactic acid molecular chains, improving interfacial compatibility; while its rigid core, together with heavy calcium carbonate, constitutes a multi-scale filling system, ensuring mechanical strength while utilizing the lubricating effect of the stearic acid layer to offset the potential decrease in processing fluidity caused by high filling amounts. Furthermore, the zinc phosphate chelate formed by nano-zinc oxide and potassium dihydrogen phosphate in the functional coating, and the Zn-S coordination bonds formed between it and residual mercapto groups on the matrix surface, ensure chemical bonding between the coating and the matrix, enabling the protective net to maintain excellent water resistance while possessing bird-attracting and self-cleaning functions.
[0042] The bird-friendly protective netting prepared in this embodiment was subjected to performance testing. The test results are as follows: tensile strength was 48.5 MPa, elongation at break was 12.3%, Escherichia coli inhibition rate was 92.5%, and Staphylococcus aureus inhibition rate was 91.8%. These data indicate that even under the lower limits of the formulation parameters, the technical solution of this application can still establish an effective synergistic reinforcement network. All key performance indicators meet the long-term use requirements of outdoor protective netting, establishing the minimum feasible boundary of the technical solution of this application.
[0043] Example 2: This example provides a production process for a bird-friendly protective net. As a preferred embodiment of this application, its process flow is the same as that of Example 1, but intermediate parameter values within the scope of the claims are used in each step to verify the robustness and optimal performance of the technical solution under the preferred process window.
[0044] This embodiment describes a manufacturing process for a bird-friendly protective net, which includes the following steps: S1. Prepare modified hemp fiber, modified nano-titanium dioxide, mercapto-modified graphene oxide, and stearic acid-modified nano-calcium carbonate for later use.
[0045] The preparation method of modified hemp fiber in S1 is as follows: The hemp fiber was immersed in a sodium hydroxide solution with a concentration of 5 g / L and boiled for 2 hours at a bath ratio of 1:20 (g / mL). After draining, it was immersed in an ethanol hydrolysate of silane coupling agent KH-560 at a bath ratio of 1:20 (g / mL) for 4 hours. After draining, it was placed in a vacuum drying oven at 50℃ and dried for 8 hours. The result is the modified hemp fiber.
[0046] The preparation method of the ethanol hydrolysate of silane coupling agent KH-560 is as follows: 1 part by weight of silane coupling agent KH-560 is dispersed in 100 parts by weight of 80% ethanol aqueous solution, stirred at 400 r / min for 30 min, then 1 part by weight of 0.1 mol / L hydrochloric acid solution is added, and stirring is continued for 10 min to obtain the ethanol hydrolysate of silane coupling agent KH-560.
[0047] The preparation method of modified nano-titanium dioxide in S1 is as follows: Ten parts by weight of nano-titanium dioxide were poured into 100 parts by weight of anhydrous ethanol and ultrasonically dispersed at 300W for 15 minutes. The pH value was then adjusted to 4.5. Next, 0.18 parts by weight of silane coupling agent KH-550 were added. The mixture was stirred at 300r / min at 65℃ for 1.5 hours. After the reaction was completed, the filtrate was removed by centrifugation and washed three times with anhydrous ethanol. The filtrate was then dried in a vacuum drying oven at 80℃ for 12 hours. The resulting product was modified nano-titanium dioxide.
[0048] The preparation method of thiolized graphene oxide in S1 is as follows: Under nitrogen protection, 1.5 parts by weight of graphene oxide and 15 parts by weight of thiourea were dissolved in 220 parts by weight of 40% hydrobromic acid solution. After stirring at room temperature for 25 min, the mixture was refluxed at 55°C for 13 h. After cooling to room temperature, the mixture was reacted at 3°C for 25 min. After adding 400 parts by weight of 20% sodium hydroxide solution, the mixture was reacted at room temperature for 8 h. The pH was adjusted to 2.5 with 10% hydrochloric acid solution, and the mixture was recrystallized with deionized water. After vacuum drying in a vacuum drying oven at 48°C for 12 h, the resulting product was thiolized graphene oxide.
[0049] The preparation method of stearic acid modified nano-calcium carbonate in S1 is as follows: 90 parts by weight of 100 nm nano-calcium carbonate were dispersed in deionized water. After uniform dispersion, 2.3 parts by weight of stearic acid were added. The mixture was heated to 90 °C and stirred at 2500 r / min for 40 min. After filtering to remove the filtrate, the mixture was washed 4 times with deionized water and dried in a 100 °C drying oven for 2.5 h. The resulting product was pulverized and passed through a 325 mesh sieve. The obtained product is stearic acid modified nano-calcium carbonate.
[0050] S2. Weigh 43 parts by weight of polylactic acid, 40 parts by weight of modified hemp fiber, 2.5 parts by weight of modified nano-titanium dioxide, 1.5 parts by weight of thiolized graphene oxide, 2.5 parts by weight of stearic acid modified nano-calcium carbonate, 10 parts by weight of heavy calcium carbonate, 0.5 parts by weight of light stabilizer, 3 parts by weight of antioxidant component, 6 parts by weight of flame retardant and 7 parts by weight of degradation regulator and mix them. Then, melt-blend and granulate the mixture at 180°C using a twin-screw extruder to obtain blended chips. The screw speed of the twin-screw extruder is 200 r / min, the length-to-diameter ratio is 28:1 and the compression ratio is 7:2.
[0051] In S2, the light stabilizer is a hindered amine light stabilizer, the antioxidant component is a compound of antioxidant 1010 and antioxidant 168 mixed in equal weight ratio, the flame retardant is a compound of aluminum hydroxide and magnesium hydroxide mixed in a weight ratio of 3:2, and the degradation regulator is potato starch.
[0052] S3. The blended chips are first pre-crystallized at 62℃ for 3.5h, and then dried at 100℃ for 15h to make the moisture content less than 0.005wt%. After drying, the chips are melt-spun at 195℃ and the initial web is obtained by drawing. The spinning speed is 1000m / min and the drawing ratio is 3. S4. Apply the functional coating liquid to the surface of the nascent net wire at a 12% impregnation coating amount. After drying, weave it into a net and tension it to set the shape. The result is a bird-friendly protective net. The drying method is to first dry it at 80°C for 5 minutes, and then bake it at 145°C for 3 minutes. During the weaving process, the coated net wire adopts a low-tension winding method to avoid coating wear.
[0053] The preparation method of the functional coating liquid in S4 is as follows: Weigh 15 parts by weight of plant essential oil microcapsule emulsion and 93 parts by weight of inorganic hydrophilic coating dispersion and mix them. Add 5 parts by weight of nano zinc oxide and stir at 700 r / min for 10 min to mix and disperse. The result is the functional coating liquid.
[0054] The preparation method of the plant essential oil microcapsule emulsion is as follows: Rosemary essential oil, peppermint essential oil and lemongrass essential oil were mixed in equal volume ratio and recorded as a plant essential oil mixture. Then, 75 parts by weight of deionized water, 12 parts by weight of the plant essential oil mixture and 3 parts by weight of sodium dodecylbenzenesulfonate were weighed and mixed. After high-speed shearing at a stirring speed of 6000 r / min for 15 min, the resulting product was the plant essential oil microcapsule emulsion.
[0055] The preparation method of inorganic hydrophilic coating dispersion is as follows: Under stirring conditions of 200 r / min, 7 parts by weight of silica sol with SiO2 content of 28% were added to 85 parts by weight of deionized water, followed by 0.2 parts by weight of sodium hexametaphosphate and 0.2 parts by weight of sodium benzenesulfonate. After adjusting the pH value to 9.2, stirring was continued for 30 min. The resulting silica hydrosol solution was obtained. Add 10 parts by weight of attapulgite to 82 parts by weight of silica hydrosol solution, stir to dissolve, then add 6 parts by weight of potassium dihydrogen phosphate and 1.5 parts by weight of sodium alginate. Stir at 900 r / min to disperse, and the resulting inorganic hydrophilic coating dispersion is obtained.
[0056] Under the intermediate parameter conditions of this embodiment, the multi-component synergistic system exhibits comprehensive performance superior to that under the lower limit parameters. This is because the proportions of each modified component and the process conditions are all within the optimal range of reaction kinetics and thermodynamic equilibrium. The dispersion state of inorganic nanoparticles in the matrix, the density of interfacial chelate bonds, and the film quality of the functional coating all reach optimal levels, thereby achieving simultaneous improvement in mechanical enhancement, functional durability, and processing stability.
[0057] The bird-friendly protective netting prepared in this embodiment was subjected to performance testing. The test results are as follows: tensile strength was 56.2 MPa, elongation at break was 15.8%, Escherichia coli inhibition rate was 96.3%, and Staphylococcus aureus inhibition rate was 95.7%. Compared with Example 1, all indicators have been significantly improved, which fully demonstrates the optimal effect of the technical solution of this application under the intermediate parameter window and eliminates the possibility that the endpoint values are accidental results.
[0058] Example 3: This example provides a production process for a bird-friendly protective net. As an implementation of the technical solution of this application within the upper limit of the claims, its process flow is the same as that of Example 1, but the upper limit of the parameter range is used in each step. The aim is to verify the stability of the multi-component synergistic system under extreme conditions such as high filler content and high reaction temperature, and to establish the maximum feasible boundary of the technical solution.
[0059] This embodiment describes a manufacturing process for a bird-friendly protective net, which includes the following steps: S1. Prepare modified hemp fiber, modified nano-titanium dioxide, mercapto-modified graphene oxide, and stearic acid-modified nano-calcium carbonate for later use.
[0060] The preparation method of modified hemp fiber in S1 is as follows: The hemp fiber was immersed in a sodium hydroxide solution with a concentration of 5 g / L and boiled for 3 hours at a bath ratio of 1:20 (g / mL). After draining, it was immersed in an ethanol hydrolysate of silane coupling agent KH-560 at a bath ratio of 1:20 (g / mL) for 4 hours. After draining, it was placed in a vacuum drying oven at 50℃ and dried for 8 hours. The result is the modified hemp fiber.
[0061] The preparation method of the ethanol hydrolysate of silane coupling agent KH-560 is as follows: 1 part by weight of silane coupling agent KH-560 is dispersed in 100 parts by weight of 80% ethanol aqueous solution, stirred at 500 r / min for 30 min, then 1 part by weight of 0.1 mol / L hydrochloric acid solution is added, and stirring is continued for 10 min to obtain the ethanol hydrolysate of silane coupling agent KH-560.
[0062] The preparation method of modified nano-titanium dioxide in S1 is as follows: Ten parts by weight of nano-titanium dioxide were poured into 100 parts by weight of anhydrous ethanol and ultrasonically dispersed at 300W for 15 minutes. The pH value was then adjusted to 5.0. Next, 0.2 parts by weight of silane coupling agent KH-550 were added. The mixture was stirred at 300r / min at 65℃ for 2 hours. After the reaction was completed, the filtrate was removed by centrifugation and washed three times with anhydrous ethanol. The filtrate was then dried in a vacuum drying oven at 80℃ for 12 hours. The resulting product was modified nano-titanium dioxide.
[0063] The preparation method of thiolized graphene oxide in S1 is as follows: Under nitrogen protection, 2 parts by weight of graphene oxide and 20 parts by weight of thiourea were dissolved in 300 parts by weight of 40% hydrobromic acid solution. After stirring at room temperature for 30 min, the mixture was refluxed at 60℃ for 15 h, cooled to room temperature, and then reacted at 5℃ for 30 min. After adding 400 parts by weight of 20% sodium hydroxide solution, the mixture was reacted at room temperature for 8 h. The pH was adjusted to 3 with 10% hydrochloric acid solution, and the mixture was recrystallized with deionized water. After vacuum drying in a vacuum drying oven at 50℃ for 12 h, the obtained product was thiolized graphene oxide.
[0064] The preparation method of stearic acid modified nano-calcium carbonate in S1 is as follows: 100 parts by weight of 200 nm nano-calcium carbonate were dispersed in deionized water. After uniform dispersion, 2.5 parts by weight of stearic acid were added. The mixture was heated to 90 °C and stirred at 2500 r / min for 40 min. After filtering to remove the filtrate, the mixture was washed 5 times with deionized water and dried in a 100 °C drying oven for 3 h. The resulting product was pulverized and passed through a 325 mesh sieve. The obtained product is stearic acid modified nano-calcium carbonate.
[0065] S2. Weigh 45 parts by weight of polylactic acid, 45 parts by weight of modified hemp fiber, 3 parts by weight of modified nano-titanium dioxide, 2 parts by weight of mercapto-modified graphene oxide, 3 parts by weight of stearic acid-modified nano-calcium carbonate, 12 parts by weight of heavy calcium carbonate, 0.7 parts by weight of light stabilizer, 5 parts by weight of antioxidant component, 7 parts by weight of flame retardant and 8 parts by weight of degradation regulator and mix them. Then, melt-blend and granulate the mixture using a twin-screw extruder at 220°C to obtain blended chips. The screw speed of the twin-screw extruder is 350 r / min, the length-to-diameter ratio is 28:1 and the compression ratio is 7:2.
[0066] In S2, the light stabilizer is a hindered amine light stabilizer, the antioxidant component is a compound of antioxidant 1010 and antioxidant 168 mixed in equal weight ratio, the flame retardant is a compound of aluminum hydroxide and magnesium hydroxide mixed in a weight ratio of 3:2, and the degradation regulator is potato starch.
[0067] S3. The blended chips are first pre-crystallized at 65℃ for 4 hours, and then dried at 100℃ for 15 hours to make the moisture content less than 0.005wt%. After drying, the chips are melt-spun at 195℃ and the initial web is obtained by drawing. The spinning speed is 1000m / min and the drawing ratio is 3. S4. Apply the functional coating liquid to the surface of the nascent net wire at a 15% impregnation coating amount. After drying, weave it into a net and tension it to set the shape. The result is a bird-friendly protective net. The drying method is to first dry it at 80°C for 5 minutes, and then bake it at 150°C for 3 minutes. During the weaving process, the coated net wire adopts a low-tension winding method to avoid coating wear.
[0068] The preparation method of the functional coating liquid in S4 is as follows: Weigh 20 parts by weight of plant essential oil microcapsule emulsion and 100 parts by weight of inorganic hydrophilic coating dispersion and mix them. Add 8 parts by weight of nano zinc oxide and stir at 800 r / min for 10 min to mix and disperse. The result is the functional coating liquid.
[0069] The preparation method of the plant essential oil microcapsule emulsion is as follows: Rosemary essential oil, peppermint essential oil and lemongrass essential oil were mixed in equal volume ratio and recorded as a plant essential oil mixture. Then, 90 parts by weight of deionized water, 20 parts by weight of the plant essential oil mixture and 4 parts by weight of sodium dodecylbenzenesulfonate were weighed and mixed. After high-speed shearing at a stirring speed of 8000 r / min for 20 min, the resulting product was the plant essential oil microcapsule emulsion.
[0070] The preparation method of inorganic hydrophilic coating dispersion is as follows: Under stirring conditions of 200 r / min, 10 parts by weight of silica sol with a SiO2 content of 30% were added to 90 parts by weight of deionized water, followed by 0.3 parts by weight of sodium hexametaphosphate and 0.3 parts by weight of sodium benzenesulfonate. After adjusting the pH value to 10.0, stirring was continued for 30 min. The resulting silica hydrosol solution was obtained. Add 15 parts by weight of attapulgite to 95 parts by weight of silica hydrosol solution, stir to dissolve, then add 10 parts by weight of potassium dihydrogen phosphate and 2 parts by weight of sodium alginate. Stir at 1000 r / min to disperse, and the resulting inorganic hydrophilic coating dispersion is obtained.
[0071] The bird-friendly protective netting prepared in this embodiment was subjected to performance testing. The test results are as follows: tensile strength was 54.8 MPa, elongation at break was 14.2%, Escherichia coli inhibition rate was 97.1%, and Staphylococcus aureus inhibition rate was 96.5%. Compared with Example 2, although the performance indicators of this embodiment fluctuated slightly under the limiting parameters, they still remained at an excellent level and were significantly better than the subsequent comparative examples. This fully demonstrates that even at the upper limit boundary of the formulation and process, the multi-component synergistic enhancement mechanism of this application remains effective, and no performance degradation or processing failure occurred, thus strongly supporting the rationality and feasibility of the scope defined by claims 1-9.
[0072] Comparative Example 1: This comparative example provides a production process for a bird-friendly protective net. The overall process is basically the same as in Example 1, with the main difference being that mercapto-modified graphene oxide is completely removed in steps S1 and S2, and replaced with an equal amount of ordinary graphene oxide. Specifically, in step S1, mercapto-modified graphene oxide is not prepared; instead, commercially available ordinary graphene oxide is used as a substitute filler. In the mixing and granulation process of step S2, 1 part by weight of mercapto-modified graphene oxide in Example 1 is replaced with 1 part by weight of ordinary graphene oxide. The remaining raw material ratios, extrusion temperature, spinning process, and coating conditions are strictly maintained consistent with those of Example 1.
[0073] The protective netting sample prepared in this comparative example underwent the same performance tests as in Example 1. The test results are as follows: the tensile strength was only 29.4 MPa, a decrease of approximately 39.4% compared to Example 1; the elongation at break was 6.8%, a decrease of approximately 44.7% compared to Example 1; after 500 hours of accelerated UV aging testing, the tensile strength retention rate was only 42.5%, far lower than the over 85% level of Example 1; the antibacterial rate against Escherichia coli was 88.2%, and the antibacterial rate against Staphylococcus aureus was 87.5%. Although it still retains some antibacterial properties, its overall mechanical properties and weather resistance cannot meet the requirements for long-term outdoor service. The precipitous drop in the above data fully confirms that once thiolized graphene oxide and the Ti-S coordination chelate bonds formed are missing, even if other components and process conditions are exactly the same, the expected technical effect cannot be obtained, thus establishing the necessity of the core technical features of this application. Comparative Example 2: This comparative example provides a production process for a bird-friendly protective net. The overall process is basically the same as in Example 1, with the main difference being that in step S1, unmodified virgin hemp fiber is directly used instead of modified hemp fiber. Specifically, in step S1, the boiling treatment with sodium hydroxide solution and the impregnation treatment with silane coupling agent KH-560 ethanol hydrolysate are omitted. Commercially available virgin hemp fiber is directly used in subsequent production after simple dust removal and drying. In step S2, 35 parts by weight of modified hemp fiber in Example 1 are replaced with 35 parts by weight of virgin hemp fiber. The remaining raw material ratios, extrusion granulation, melt spinning, and functional coating conditions are strictly maintained consistent with those in Example 1.
[0074] The protective netting sample prepared in this comparative example underwent the same performance tests as in Example 1. The test results are as follows: the tensile strength was only 32.6 MPa, a decrease of approximately 32.8% compared to Example 1; the elongation at break was 7.5%, a decrease of approximately 39.0% compared to Example 1; the notched impact strength of the simply supported beam was only 3.8 kJ / m², far lower than the 8.2 kJ / m² of Example 1, a decrease of up to 53.7%; the inhibition rate against Escherichia coli was 91.2%, and the inhibition rate against Staphylococcus aureus was 90.5%. Although it maintained good antibacterial properties due to the unchanged coating system, the severe deterioration of its mechanical properties rendered it completely unusable as an outdoor protective netting. The above data, especially the precipitous drop in impact toughness, directly reveals the fragility of the interfacial bond between the unmodified hemp fiber and the polylactic acid matrix, fully demonstrating the non-obviousness of the hemp fiber modification step in this application and its key contribution to improving the overall performance of the protective netting.
[0075] Comparative Example 3: This comparative example provides a production process for a bird-friendly protective net. The overall process is basically the same as in Example 1, with the main difference being that nano-zinc oxide is not added at all during step S4 when preparing the functional coating liquid. Specifically, in step S4, only 10 parts by weight of plant essential oil microcapsule emulsion and 85 parts by weight of inorganic hydrophilic coating dispersion are mixed and stirred at 600 r / min for 10 min to achieve the desired dispersion. The resulting functional coating liquid does not contain nano-zinc oxide. The remaining raw material ratios, extrusion granulation, melt spinning, and drying and setting conditions are strictly maintained consistent with those in Example 1.
[0076] The protective netting sample prepared in this comparative example underwent the same performance tests as in Example 1. The test results are as follows: the tensile strength was 47.8 MPa, and the elongation at break was 12.0%. Although these results were similar to those in Example 1 due to the unchanged matrix formulation, the functional indicators showed severe deterioration. The antibacterial rate against Escherichia coli decreased to 65.4%, and the antibacterial rate against Staphylococcus aureus decreased to 62.1%, far lower than the level of over 90% in Example 1. The coating adhesion (number of washes) was only 8 times, a decrease of more than 84% compared to over 50 times in Example 1. The effective period of the bird-attracting component (based on the effective volatile matter concentration threshold) was only 2.5 months, less than a quarter of that in Example 1 (over 12 months). The above data clearly reveal the complete collapse of the coating system in terms of interfacial bonding, structural integrity, and functional slow-release regulation capability after the absence of nano-zinc oxide. This fully demonstrates the necessity of the ternary synergistic system of functional coatings in this application and its key contribution to improving the overall service performance of the protective netting.
[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A manufacturing process for a bird-friendly protective net, characterized in that, The production process includes the following steps: S1. Prepare modified hemp fiber, modified nano-titanium dioxide, mercapto-modified graphene oxide and stearic acid-modified nano-calcium carbonate for later use. S2. Weigh 40-45 parts by weight of polylactic acid, 35-45 parts by weight of modified hemp fiber, 2-3 parts by weight of modified nano-titanium dioxide, 1-2 parts by weight of thiolized graphene oxide, 2-3 parts by weight of stearic acid modified nano-calcium carbonate, 8-12 parts by weight of heavy calcium carbonate, 0.2-0.7 parts by weight of light stabilizer, 1-5 parts by weight of antioxidant component, 5-7 parts by weight of flame retardant and 5-8 parts by weight of degradation regulator, and mix them. Then, melt-blend and granulate the mixture using a twin-screw extruder at 150-220℃ to obtain blended chips. S3. After drying the blended chips, melt spinning is performed at a temperature of 195°C, and the resulting yarn is drawn to obtain the initial web. S4. Apply the functional coating liquid to the surface of the nascent netting, dry it, weave it into a net, and then tension and shape it to obtain the bird-friendly protective netting.
2. The manufacturing process of a bird-friendly protective net according to claim 1, characterized in that, The preparation method of modified hemp fiber in S1 is as follows: The hemp fiber was immersed in a sodium hydroxide solution with a concentration of 5 g / L at a bath ratio of 1:20 and boiled for 1-3 hours. After draining, it was immersed in an ethanol hydrolysate of silane coupling agent KH-560 at a bath ratio of 1:
20. After impregnation treatment, it was drained and vacuum dried in a drying oven. The result is the modified hemp fiber.
3. The manufacturing process of a bird-friendly protective net according to claim 1, characterized in that, The preparation method of modified nano-titanium dioxide in S1 is as follows: Ten parts by weight of nano-titanium dioxide were poured into 100 parts by weight of anhydrous ethanol. After ultrasonic dispersion, the pH value was adjusted to 4.0-5.
0. Then, 0.15-0.2 parts by weight of silane coupling agent KH-550 were added. The mixture was stirred and reacted at 65°C. After the reaction was completed, the filtrate was removed by centrifugation and washed three times with anhydrous ethanol. After vacuum drying, the modified nano-titanium dioxide was obtained.
4. The manufacturing process of a bird-friendly protective net according to claim 1, characterized in that, The preparation method of thiolized graphene oxide in S1 is as follows: Under nitrogen protection, 1-2 parts by weight of graphene oxide and 10-20 parts by weight of thiourea are dissolved in 150-300 parts by weight of hydrobromic acid solution. After stirring at room temperature for 20-30 minutes, the mixture is refluxed at 50-60℃ for 12-15 hours. After cooling to room temperature, the mixture is reacted at 0-5℃ for 20-30 minutes. 400 parts by weight of 20% sodium hydroxide solution are added, and the mixture is reacted at room temperature for 8 hours. After adjusting the pH to 2-3, the mixture is recrystallized with deionized water and dried under vacuum to obtain thiolized graphene oxide.
5. The manufacturing process of a bird-friendly protective net according to claim 1, characterized in that, The preparation method of stearic acid modified nano-calcium carbonate in S1 is as follows: Weigh 80-100 parts by weight of nano-calcium carbonate and disperse it in deionized water. After the dispersion is uniform, add 2.1-2.5 parts by weight of stearic acid. Heat to 90℃ and stir at 2500r / min for 40min. After filtering to remove the filtrate, wash with deionized water 3-5 times, dry, pulverize and sieve. The result is stearic acid modified nano-calcium carbonate.
6. The manufacturing process of a bird-friendly protective net according to claim 1, characterized in that, In S2, the light stabilizer is a hindered amine light stabilizer, the antioxidant component is a compound of antioxidant 1010 and antioxidant 168 mixed in equal weight ratio, the flame retardant is a compound of aluminum hydroxide and magnesium hydroxide mixed in a weight ratio of 3:2, and the degradation regulator is potato starch.
7. The manufacturing process of a bird-friendly protective net according to claim 1, characterized in that, The preparation method of the functional coating liquid in S4 is as follows: Weigh 10-20 parts by weight of plant essential oil microcapsule emulsion and 85-100 parts by weight of inorganic hydrophilic coating dispersion, mix them together, add 2-8 parts by weight of nano zinc oxide and mix and disperse. The result is the functional coating liquid.
8. The manufacturing process of a bird-friendly protective net according to claim 7, characterized in that, The preparation method of the plant essential oil microcapsule emulsion is as follows: Rosemary essential oil, peppermint essential oil, and lemongrass essential oil are mixed in equal volume ratios and recorded as a plant essential oil mixture. Then, 60-90 parts by weight of deionized water, 5-20 parts by weight of the plant essential oil mixture, and 1-4 parts by weight of sodium dodecylbenzenesulfonate are weighed and mixed. After high-speed shearing, the resulting product is a plant essential oil microcapsule emulsion.
9. The manufacturing process of a bird-friendly protective net according to claim 7, characterized in that, The preparation method of the inorganic hydrophilic coating dispersion is as follows: Add 5-15 parts by weight of attapulgite to 70-95 parts by weight of silica hydrosol solution, stir to dissolve, then add 3-10 parts by weight of potassium dihydrogen phosphate and 1-2 parts by weight of sodium alginate, stir to disperse, and the resulting inorganic hydrophilic coating dispersion is obtained.
10. A bird-friendly protective net, characterized in that, It is manufactured using the production process of any one of claims 1-9 for a bird-friendly protective net.